2019
DOI: 10.1101/662643
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Integrating population genetics to define conservation units from the core to the edge ofRhinolophus ferrumequinumwestern range

Abstract: The greater horseshoe bat (Rhinolophus ferrumequinum) is among the most widespread bat species in Europe but it has experienced severe declines, especially in Northern Europe. This species is listed Near Threatened in the European IUCN Red List of Threatened Animals and it is considered to be highly sensitive to human activities and particularly to habitat fragmentation. Therefore, understanding the population boundaries and demographic history of populations of this species is of primary importance to assess … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 81 publications
0
2
0
Order By: Relevance
“…In particular, it is critical to assess whether these variations might significantly impact the demography and viability of R. ferrumequinum populations (Schweiger et al., 2015). This is all the more important given that it has recently been shown that some populations at the edge of the R. ferrumequinum distribution might be at higher risk of extinction in the near future (Tournayre et al., 2019).…”
Section: Discussionmentioning
confidence: 99%
“…In particular, it is critical to assess whether these variations might significantly impact the demography and viability of R. ferrumequinum populations (Schweiger et al., 2015). This is all the more important given that it has recently been shown that some populations at the edge of the R. ferrumequinum distribution might be at higher risk of extinction in the near future (Tournayre et al., 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Four species of amphibians, Triturus marmoratus, Hyla meridionalis, Epidalea calamita and Pelodytes punctatus were considered for a low dispersal group, and Rhinolophus ferrumequinum, Miniopterus schreibersii, Nyctalus leisleri and Pipistrellus pipistrellus, for a high dispersal group. While estimating the dispersal distances of species is challenging and may lead to underestimates (Santini et al 2013;Fonte et al 2019;Tournayre et al 2019), we deliberately performed our analyses while taking into account long distances for both groups. The aim was to consider the different life cycle processes of the species such as dispersal and migration (Runge et al 2014).…”
Section: Study Species and Dispersal Groupsmentioning
confidence: 99%